Implementation and Experiences of Participating in a Neurologic Service Learning Clinic in a Physical Therapist Entry-Level Program: An Educational Case Report. Issue 4 (December 2019) - Danzl, Megan; Ulanowski, Elizabeth; Carta, Taylor; Bridges, Ylice; Conway, Devin; Vessels, Lexi
Abstract : Background and Purpose: The integration of service learning (SL) in physical therapist entry-level education is a way of serving the community while also meeting curricular demands. Educational programs have successfully implemented service learning clinics (SLCs) while positively affecting the development of professionalism. Research examining specialized SLCs in programs is only just emerging. This case report describes the implementation and experiences of participating in a neurologic-specific SLC. Case Description: Through a partnership between the program and a local hospital, faculty, students, and members of the hospital rehabilitation leadership developed and implemented a neurologic SLC. Over the first year, 37 first- and second-year students participated. Twice a week, student dyads (first- and second-year pairs) treated patients with a neurologic diagnosis. Student reflection papers were qualitatively examined to understand the students' experiences. Outcomes: Three themes emerged: 1) "Find my 'PT Self'": Professional Growth, 2) "Out of my comfort zone": Challenges for Novices, and 3) "Out of the books and into the real world": Bringing Curriculum to Life. Discussion and Conclusion: The SLC afforded students the opportunity to treat individuals with neurological disorders, reinforce coursework, and further prepare for patient care in a neurological setting. Data regarding the value of student learning and the perceived challenges for novices will inform other programs interested in integrating SL into the curriculum, particularly a neurologic-specific experience.